Applying the concept of foresight method for building tourism destination management scenarios - Walas, Bartłomiej; Borzyszkowski, Jacek; Fedyk, Wojciech; Bagińska, Justyna; Głuc, Marcin (Bulletin of Geography. Socio-economic Series, 2025)
The article presents a methodological concept for the creation of tourism management foresight scenarios for selected areas of intervention and driving forces as well as the obligatory components influencing the directions of its evolution. Recommendations were made on methods and research techniques for preparing such a scenario. The proposed concept of creating foresight of positive and negative future events or situations will enable stakeholders and decision-makers to evaluate what effect the foreseen transformation should have on the management of a destination, which will result in new organizational, financial and legal tools within the framework of the tourism policy of the country or region. The scenarios identify the network of agents of change and the expected benefits and facilitate a continuous diagnostic of the state of the tourism function in the destination and further evolution from the perspectives of diverse stakeholder types.